C-Reactive Protein and Carotid Intima-Media Thickness in Children with Sleep Disordered Breathing - Iannuzzi, Arcangelo (American Academy of Sleep Medicine, 2013)
STUDY OBJECTIVES: Obesity is a risk factor for sleep disordered breathing (SDB) in children. Plasma levels of high-sensitivity C-reactive protein (Hs-CRP) are predictive of cardiovascular morbidity in adults, and CRP levels are associated with over-weight. Increased carotid intima-media thickness (IMT) is associated with several cardiovascular risk factors. We evaluated the effect of SDB on CRP levels and IMT in lean and obese children not selected for snoring. METHODS: 101 children (age 5-15 years) attending a weight clinic or scheduled for routine visit. IMT was measured with quantitative B-mode ultrasound scans. The apnea-hypopnea index (AHI) was measured overnight: AHI < 1 defined controls, AHI ≥ 1 to < 5 = mild SDB, and AHI ≥ 5 = obstructive sleep apnea (OSA). RESULTS: AHI was significantly associated with Hs-CRP concentration (r = 0.32, p = 0.002) in all 101 children irrespective of age and sex. Body mass index (BMI) was higher in OSA children than controls (25.5 ± 7.0 vs 22.1 ± 6.9, p = 0.05). Obese children had 3.3 times more probability of having OSA (HR 3.3, 95% CI 1.2-9.3, p = 0.02) than lean children. Hs-CRP values were significantly higher in children with OSA than in children without (p = 0.011), but not when BMI z-score was added as covariate. IMT was not associated with AHI or SDB. CONCLUSIONS: The results of this study suggest an association between OSA and Hs-CRP concentrations (mainly mediated by overweight and obesity), but not between OSA and subclinical atherosclerosis. There is scope for prevention in childhood before OSA syndrome causes the irreversible damage to arteries observed in adult patients. CITATION: Iannuzzi A; Licenziati MR; De Michele F; Verga MC; Santoriello C; Di Buono L; Renis M; Lembo L; D'Agostino B; Cappetta D; Polverino M; Polverino F. C-reactive protein and carotid intima-media thickness in children with sleep disordered breathing. J Clin Sleep Med 2013;9(5):493-498.